OPTIMALISASI KAPASITAS GERBANG TOL SEMANGGI I DAN SEMANGGI II TERHADAP PANJANG ANTRIAN KENDARAAN - Achmad Nadjam; NURRIFAI NURRIFAI; ACHMAD ADYATMOKO (Jurnal Poli-Teknologi, 2013)
Research on optimization of the capacity of toll gate semanggi 1 and 2 to long queues of vehicles is done by the queue theory approach and the capacity of the toll gate. Calculation of additional substation on the optimal number of toll gate semanggi 1 and 2 uses multiserver queuing theory. To address the causes of the most dominant variable in the long queue of vehicles is done by statistical tests. Increasing the number of substations which is done must be adjusted by the number of long queues of vehicles that are allowed by the minister for state owned company is 5 vehicles. The research methodology used is to conduct a survey of service time, the volume of vehicular traffic, the caused of the long queues of vehicles and open-close timing of toll gate semanggi 1. Based on the analysis obtained by calculating the optimal number of substations, based on normal conditions, changes in payment mechanisms and arrangements open and close toll gates semanggi 1 variable causes the most dominant long queue which is dated within one month of the service time of the transaction, a large nominal payment to the substation as well as the date of service time in 1 month and non-normal behavior of users jointly affect the service time of transactions. The result is the calculation of the optimal number of substations based on the change in payment mechanism at toll gate semanggi 1 with 3 main substations, while the toll gate semanggi 2 with 4 main substations. The optimum number of substations based on normal conditions at toll gate semanggi 1 are 4 main substations, while the toll gate semanggi 2 are 2 main substations and 2 tandem substations, while the number of substations based on the optimal open-close system at toll gate semanggi 1, at toll gate clover 1 is 4 main substations, while at toll gate semanggi 2 by 4 main substations. The timing for the opening and closing of toll gate semanggi 1 is 11 minutes for closing time, and 49 minutes for every hour of time in the open condition. Key words: optimization, toll gate capacity, queuing vehicles